El factoring y su incidencia en la liquidez de las empresas de revisiones técnicas de embarcaciones del puerto de Salaverry - Rabanal Vigo, Luz Eufemia (2018)
The present research has been developed with the purpose of determining the incidence of the factoring in the liquidity of the companies of technical reviews of ships of the Port of Salaverry. For the development of this research, the inductive, descriptive and analytical method has been used. It starting from a particular fact to reach general conclusions and the data was collected through direct observation without manipulating them. Also, has been used observation and documentary analysis. In the development and evaluation of the results has been taken the financial information of the company GLR S.A.C. for that the analysis of financial statements was carried out through liquidity ratios, comparing the results obtained with and without factoring in 2015 and 2016 respectively, concluding that factoring has a positive impact on the liquidity of companies in technical reviews of ships of the Port of Salaverry. According to the results obtained, it is recommended to the companies of the technical reviews of ship of Port of Salaverry the application of factoring as a tool to improve the liquidity indexes and reduce the risk of uncollectibility, since it allows the recovery of cash flows from fastest way.